ANTIBACTERIAL ACTIVITY TEST SEA CUCUMBER EXTRACT (Holothuria scabra) SIDAYU COAST GRESIK USING DISK DIFFUSION METHOD - Arifin, Haris Nursyah; Ningsih, Rachmawati; Fitrianingsih, Avin Ainur; Hakim, Abdul (ALCHEMY, 2013)
Sea cucumber (Holothuria scabra) is one kind of sea cucumbers that contains of bioactive compound that can inhibit bacteria growth. This research aim to know the effect of methanol and n-hexane extract towards bacterium Staphylococcus aureus, Salmonella typhi and Escherichia coli bacterial growth and to identification estimation active compound group.Sea cucumbers active compound extraction using maceration method with methanol and n-hexane as a solvent. Methanol and n-hexane crude extract conducted antibacterial assay using disk diffusion method towards bacterium Staphylococcus aureus, Salmonella typhi, Escherichia coli and continued with reagent test to knowing active compound group.The result of this research indicated that n-hexane extracts provide the best inhibition zone toward bacterium Escherichia coli at concentration 2000 ppm with among of inhibition zone 1,75 mm, while at bacterium Staphylococcus aureus and Salmonella typhi does not provide inhibition zone. Methanol extract does not provide inhibition zone towards bacterium Staphylococcus aureus, Salmonella typhi and Escherichia coli. The result of reagent test indicated compound that detected in n-hexane extract is saponins